Evaluation of Potentially Inappropriate Medication Use and Risk of Adverse Drug Reactions in Hospitalized Older Adults: An Observational Study in a Tertiary Care Hospital - Rawat, Rohit Singh (Indian Journal of Pharmacy Practice)
Background and Objectives: The older population are more vulnerable to inappropriate prescribing andrelated adverse events due altered physiology. The objectives of the present study were to determine the prevalence of potentially inappropriate medication use in hospitalized older adults and assess its relationship with adverse drug reactions. Method: This is a prospective, observational, study conducted in the medicine wards of Shri Mahant Indiresh Hospital, Dehradun, and Uttarakhand, India after obtaining approval of the Institutional Ethics Committee. A sample of 112 elderly patients (60 years and above) were included during the study period of 5 months. Inappropriate medications were identified by using 2015 updated Beers Criteria. Causality of the adverse events was assessed by Naranjo Adverse Drug Reaction Probability Scale. Results: It was found that at least one potentially inappropriate medication was received by 32.14% (36) patients. A total of 31 adverse drug reactions were observed in 30 patients. Of these, 13 (41.9%) were observed in 12 patients were due to inappropriate medications listed in 2015 updated Beers Criteria. No statistically significant association was found between adverse drug reactions and use of potentially inappropriate medications [χ2 = 1.16, P = 0.281] [Odds ratio (OR): 1.61 {95% confidence interval (CI): 0.67:3.85} P = 0.283]. Clonidine, clonazepam and sliding scale use ofinsulin were found to be most common inappropriately prescribed medications. Conclusion: The study shows that there is high prevalence of potentially inappropriate prescribing and adverse drug reactions among the hospitalized older adults in medicine wards.
Keywords: Elderly patients; Older adults; Beers criteria; Potentially inappropriate medications; Adverse drug reactions.